2007
DOI: 10.1007/s10608-006-9086-x
|View full text |Cite
|
Sign up to set email alerts
|

Desire for Control, Sense of Control and Obsessive-Compulsive Symptoms

Abstract: While control-related cognitions have often been implicated in discussions of Obsessive Compulsive Disorder (OCD), empirical investigations of the relationship between control-constructs and OCD symptoms have been relatively limited. In this article it was hypothesized that OCD symptoms may be linked with a higher desire to control (DC), but a lower sense of control (SC) over the self and environment, leading to motivation for compulsive symptoms. This hypothesis was investigated in an analogue population, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 57 publications
(61 reference statements)
8
35
0
1
Order By: Relevance
“…Interestingly, no OCD symptoms were found to be correlated with an increased experience of control; moreover, only the checking symptoms were related to an undermined sense of control. This result is in agreement with a recent study in which selfreported low sense of control was found to be particularly related to checking symptoms [48]. In the task used by Reuven-Magril et al [50], feelings of control were predominantly elicited by the effortful control situation created by the design of the task.…”
Section: Summary and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, no OCD symptoms were found to be correlated with an increased experience of control; moreover, only the checking symptoms were related to an undermined sense of control. This result is in agreement with a recent study in which selfreported low sense of control was found to be particularly related to checking symptoms [48]. In the task used by Reuven-Magril et al [50], feelings of control were predominantly elicited by the effortful control situation created by the design of the task.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…However, other studies showed that they can experience a high sense of control [45] or have a higher need for control [46]. These conflicting results have been interpreted as reflecting the fact that, in response to their undermined sense of control, some OCD individuals may deploy compulsions to regain control over their actions or over unwanted events [47,48]. From this perspective, compulsive behaviors can be viewed as a way of artificially inflating affected individuals' feelings of control, when the mechanism underlying a "naturally occurring" sense of control breaks down [49,50].…”
Section: Sense Of Agency In Ocd: Empirical Datamentioning
confidence: 99%
“…Thus, an alternative explanation of our results would be that the relationship observed between authorship ascription and checking symptoms could be mediated by control beliefs such as self-determination, which have recently been found to constitute an additional source of information for authorship processing (Aarts, Oikawa, & Oikawa, 2010). Consistently with this idea, OCD symptoms, and particularly checking symptoms, may be related to an undermined perceived control (beliefs about one's ability to perform an action and the extent to which that action will lead to a desired outcome or avoid an undesirable one; Moulding & Kyrios, 2007). Thus, further studies are needed to explore the extent to which beliefs of control and self-determination may account, at least in part, for the relationship found between checking symptoms and lower self-agency.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, on the other hand, the illusion of agency task elicited a sense of effortless control and thus feelings of self-causation were predominantly based on automatic and unconscious processes, similar to those observed during nonconscious goal pursuit (Aarts et al, 2005, 2006). Furthermore, a recent cognitive model of OCD (Moulding & Kyrios, 2006, 2007 suggests the involvement of two controlrelated features: the need for control (i.e., the general motivation to be able to exert control over events) and the sense of control (i.e., beliefs in one's ability to attain or avoid specific outcomes through one's actions). According to this model, the level of desired control generally leads to the deployment of appropriate behaviors in order to achieve desired outcomes; the level of perceived control in a specific context may vary accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation